Physicochemical Investigation of Lanthanon(III) Chelates of Multidentates Possessing N, O, O Donors - Sharma, A.; Jain, L.; Sharma, S.; Kacchwah, G.R.; Jangid, S.; Mehta, R.K. (Asian Journal of Chemistry, 2010)
The dissociation constants of O-(N-O-hydroxy benzophenimino) benzoic acid (H2 BB) and O-(N-O-hydroxy benzo-phenimino) propanoic acid (H2BP') and thermodynamic stability constants of their chelates with La(III), Ce(III), Pr(III), Nd(III), Sm(III). Gd(III), Tb(III). Dy(III) Ho(III) and Er(III) were determined by Calvin-Bjerrum pH titration technique as modified by Irving. Rossotti method in 30% (v/v) dioxane water media (μ ═ 0.01 N. 0.05 M and 0.1 M NaClO4). The solid Ln(III)-chelates were characterised by physico-chemical techniques and stereochemistry established.